2000
DOI: 10.2118/62041-pa
|View full text |Cite
|
Sign up to set email alerts
|

Unique ESP Completion and Perforation Method Maximizes Production in World Record Step-Out Well

Abstract: Summary In this article we describe the key planning and operational experiences gained during the perforation and completion phases of the world record step-out extended reach well at the Wytch Farm oilfield in Dorset, England. We present an overview of how the M-11 well was completed successfully and describe how a combination of existing and new technology was applied to achieve Wytch Farm's most prolific producer. Well 1M-11SPy (M-11) the world record for the highest hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…in some fields, horizontal wells may need to be cased and perforated. Selective perforating have been implemented in the horizontal wells drilled in many fields such as Bongkot, 1 Joanne, 2 Andrew, 3 Oseberg, [4][5] Wytch Farm, 6 Statfjord, 7 Elk Hills, 8 Beryl, 9 Dan, 10 Alba, 11 Yowlumne, 12 and Prudhoe Bay. 13 In the Bongkot Field, the deviated wells were perforated across multiple reservoirs and equipped with sliding sleeves to allow selective production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in some fields, horizontal wells may need to be cased and perforated. Selective perforating have been implemented in the horizontal wells drilled in many fields such as Bongkot, 1 Joanne, 2 Andrew, 3 Oseberg, [4][5] Wytch Farm, 6 Statfjord, 7 Elk Hills, 8 Beryl, 9 Dan, 10 Alba, 11 Yowlumne, 12 and Prudhoe Bay. 13 In the Bongkot Field, the deviated wells were perforated across multiple reservoirs and equipped with sliding sleeves to allow selective production.…”
Section: Introductionmentioning
confidence: 99%
“…gun with 6 spf at the poorer quality sands. 6 Production logs have indicated that some of the perforated intervals are not contributing to production.…”
Section: Introductionmentioning
confidence: 99%